Strategi CSR Bank Jatim Berupa Mobil Ambulans Untuk Meningkatkan Layanan Kesehatan ASN dan Mewujudkan Perubahan Sosial Berkelanjutan - Octavianto, Shiena; Arumsari, Devinta (Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
This article examines the strategy of Corporate Social Responsibility (CSR) of Bank Jatim through the program of providing ambulance assistance. This program aims to improve the health services of the State Civil Apparatus (ASN) and realize sustainable social change in East Java. The research method used is qualitative non-interactive, with a focus on the analysis of documents related to the CSR of Bank East Java. The article shows that providing ambulances is part of the